THE RUINS OF LOVE: IBN ‘ARABI’S POETICS OF PERPLEXITY - Yiangou, Nikos (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2012)
Muhyiddin Ibn 'Arabi is renowned for his voluminous output of works on almost every subject, including theology, cosmology, jurisprudence, philosophy and the mystical sciences, numbering some 350 works. What is less known is the fact that he was also a prodigious and talented poet, with an output of several thousand poems. While he describes in great detail the phenomenology and ontological exegesis of his mystical experiences in works such as the FutÅ«hÄt al-Makkiyya, it is in his poetry where the expression of his passionate love for his beloved is revealed in its full humanity. The condition of one who has passed from separation to union, tawhid, is revealed through his poetry to be intensely alive, traversing the full range of bliss and loss that lovers know all too well, for his beloved is to be found in every thing, yet cannot be contained by any thing, hence never to be possessed.